1996
DOI: 10.1021/bi960989v
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Channel Properties of the Uncoupling Protein from Brown Adipose Tissue Mitochondria:  A Patch-Clamp Study

Abstract: The uncoupling protein (UCP) from brown adipose tissue mitochondria possesses H+ and Cl- transport activities [reviewed in Klingenberg, M. (1990) Trends Biochem. Sci. 15, 108-112]. Being a member of a mitochondrial carrier family, the transport of H+ and Cl- is carrier-like, i.e., much slower as compared to channels. Here we report that UCP reconstituted into giant liposomes displays stable chloride channel properties under patch-clamp conditions. The transport inhibitors (GTP, GDP, ATP, and ADP) also inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 53 publications
(87 reference statements)
3
56
0
Order By: Relevance
“…Thus, modi cation of one type of residues led to inhibition of transport while modi cation of another type led to a major loss of transport speci city, and it seemed to convert the carrier into a pore-like state (11)(12)(13). These channel-like properties were later con rmed by patch-clamp experiments that described conductances of up to 600 pS in the AAC (14) and lower but signi cant levels in the PiC (15) and UCP1 (16). All these results have been taken as an indication of the existence of at least two different functional domains in these carriers: one responsible for the carrier properties and another that confers channel-like properties (17)(18)(19).…”
Section: Introductionmentioning
confidence: 94%
“…Thus, modi cation of one type of residues led to inhibition of transport while modi cation of another type led to a major loss of transport speci city, and it seemed to convert the carrier into a pore-like state (11)(12)(13). These channel-like properties were later con rmed by patch-clamp experiments that described conductances of up to 600 pS in the AAC (14) and lower but signi cant levels in the PiC (15) and UCP1 (16). All these results have been taken as an indication of the existence of at least two different functional domains in these carriers: one responsible for the carrier properties and another that confers channel-like properties (17)(18)(19).…”
Section: Introductionmentioning
confidence: 94%
“…A 75pS anion channel was recorded in giant liposomes reconstituted with UCP1 (88), and reconstitution of the individual transmembrane domains of human UCP2 showed that all six transmembrane peptides form helical conformations in lipid model membranes. Only the second transmembrane peptide exhibited voltage-dependent anion channel behavior (89).…”
Section: Proton Leak and Uncoupling Proteinmentioning
confidence: 99%
“…UCP 1 transcripts in BAT have been determined by using Northern blot analysis, and the UCP 1 protein has usually been detected by using polyclonal antibodies specific for the fulllength protein. In addition, UCP 1 abundance in BAT (12)(13)(14) and the degree of masking (binding sites already occupied) of the purine nucleotide-binding sites (15) have been measured by binding of labeled GDP to mitochondria. To date, UCP 1 protein has not been found in any tissue other than BAT, although it has been sought in liver, heart, epididymal white adipose tissue, parametrial white adipose tissue, and thigh muscle (4,16); and a previous study, using Northern blot analysis, failed to detect UCP 1 transcripts in thymus (17).…”
mentioning
confidence: 99%